Coping Mechanisms in Dealing with Dual Role Stress among Health Cadres Who Have Many Jobs - Laila Ulfiyana; Arum Pratiwi (Jurnal Keperawatan Profesional, 2026)
Indonesian women who carry out dual roles as housewives and posyandu cadres have the potential to experience stress due to domestic, social, and economic demands. As health volunteers, Posyandu cadres are required to carry out various service tasks with limited resources and compensation, so it has the potential to increase stress. This condition reflects the complexity of the responsibilities faced by Posyandu cadres in balancing the demands of family and community services. This study aims to explore the experiences and coping strategies used by posyandu cadres when facing role stress. This type of research is qualitative with a phenomenological approach Five participants were selected through purposive sampling. Researchers collected data through in-depth interviews, field notes, and documentation. The researcher analyzed the data using the Colaizzi method thematically. The results of the study identified four main themes, namely stress-triggering factors which include domestic workload, dual roles as cadres, economic pressure, and lack of family support; stress reactions that include emotional, physical, social, and spiritual responses; coping strategies that include religious coping mechanisms, social support, emotion regulation, and rearrangement of activities; and the meaning of stress as a test, moral responsibility, and the process of self-maturation. This study concludes that stress in posyandu cadres is multidimensional and requires psychosocial support and stress management training to strengthen adaptive coping skills.